Tayma, Saudi-Arabien: Bauforschung am Qasr al-Radm - Knop, Cindy; Hausleiter, Arnulf (e-Forschungsberichte des DAI, 2023)
In the frame of the Saudi-German collaborative project at Tayma, one of the best preserved pre-Islamic buildings at the oasis of Tayma, known as Qasr al-Radm, was systematically investigated for the first time. Altogether six building phases have been identified. The large rock-cut well may be much older than the main part of the structure, which is probably a 4th/5th century AD construction. By partly dismantling the latter a camel draw was added to it in a time after the visit of Julius Euting to Tayma in 1884, who produced a sketch drawing of the then complete building.